A novel prognostic related lncRNA signature associated with amino acid metabolism in glioma - Lei, Qiang; Yuan, Bo; Liu, Kun; Peng, Li; Xia, Zhiwei (Frontiers in Immunology, 2023)
Glioma is one of the deadliest malignant brain tumors in adults, which is highly invasive and has a poor prognosis, and long noncoding RNAs(lncRNAs) have key roles in the progression of glioma. Amino acid metabolism reprogramming is an emerging hallmark in cancer. However, the diverse amino acid metabolism programmes and prognostic value remain unclear during glioma progression. Thus, we aim to find potential amino-related prognostic glioma hub genes, elaborate and verify their functions., and explore further the impact on glioma.